Thermal Validation, Structural Implications and Redesign Proposals of the Multipurpose External Dump of the Proton Synchrotron at CERN. Issue 3 (21st February 2021) - Pilan Zanoni, André; Calviani, Marco; Grenier-Boley, Edouard
Abstract: In order to safely absorb charged particle beams prepared for various experimental facilities at the European Organization for Nuclear Research (CERN) an external dump is installed at the end of the Proton Synchrotron (PS) transfer line. This dump currently consists of stacked cast iron blocks surrounded by concrete shielding. This paper analyzes the thermal performance of the PS external dump under today's most critical beam operational scenarios. Thermal analysis using preliminary material models will be correlated with in-site thermal measurements on the open face of the dump. From this analysis we conclude on the thermal and structural consequences of further operation of the dump under current and future beam-operation scenarios in which beam intensities are expected to increase by a factor of three. Finally we analyze a new design proposal with active cooling for the consolidation of the PS external dump.